Systemic Functional Linguistics: Mood System and Transitivity of Fast-Food Restaurant Slogans - Muhyidin, Mohammad (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2025)
This study aims to find out types of mood systems and systems of transitivity used in fast food restaurant slogans and to find out how fast food restaurant slogans use mood systems and transitivity. The researcher used a descriptive qualitative design. The researcher takes McDonald’s, KFC, Burger King, Subway, and Pizza Hut as slogans. There are four types of mood systems, namely declarative, imperative, interrogative and exclamative. Based on the analysis of the slogans used in fast food restaurant, the most dominant types used is declarative mood (73,7%), while the second types is imperative mood (15,8%), the third place is interrogative mood (10,5%), and there is no exclamative mood (0%). According to analysis of the transitivity system based on Halliday’s theory, the result of this analysis found material processes (47,4%) is the most dominant process, while relational processes (36,8%), mental processes (15,8%), and there is no verbal, behavioural and existential processes used in fast food restaurant slogans. Based on Halliday’s theory, mood types have their own function in the clause. Mostly, the function of the slogans is found in the declarative mood, is the writer (companies) conveys the information and makes a statement to the reader (customer). While imperative mood is found in fast food restaurant slogans also has a function. Its function is for the writer (companies) to convey the command and order to the reader (customer). Although interrogative only two clauses are found in fast food restaurant slogans, it function is the writer (companies) asks the question to the reader (customer).